Penerapan Peta Strategi dan Balance Scorecard untuk Meningkatkan Kinerja Manajemen (Studi Kasus pada Rumah Sakit Khusus Jiwa Soeprapto Provinsi Bengkulu) - Marietza, Fenny; Agesty, Fallen (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2023)
The COVID-19 pandemic has brought about a marked slowdown in global economic development. Institutions must adopt new managerial guidelines to adapt to the difficult conditions of the current pandemic, including in the service sector, namely hospitals. The occurrence of an increase in patients at the Bengkulu Province Mental Special Hospital became the backgroundÂ of this study. Improved managerial performance in hospitals is assisted by the implementation of strategy maps and balanced scorecards. This study aims to find out how to implement a strategic map that includes vision, mission and goals as well as four perspectives of a balanced scorecard containing finance, customers, internal business processes and learning growth which are analyzed using SWOT analysis to improve the management performance of the Bengkulu Province Mental Hospital.Â This study used a qualitative approach by collecting secondary data and primary data by interviewing four informants who participated in managing and implementing the hospital’s strategy map and balanced scorecard. Based on the research that has been done at Soeprapto Mental Hospital Bengkulu and analyzed, it can be concluded that the strategy map is of good value because it is able to realize and link the vision, mission and goals of Soeprapto Mental Hospital Bengkulu. The balance scorecard is of good value because it is able to explain the positive relationship between Â the Â strategy Â map Â and Â the Â fourÂ perspectives Â of Â the Â balanced Â scorecard. Â SWOT analysis as a method of measuring the balance scorecard is of good value because it is able to Â analyzeÂ strengths, Â weaknesses, Â threats Â and Â opportunities Â that Â can Â occur Â next. Â In conclusion, the strategy map and balanced scorecard to improve management performance are of good value because they are able to explain the interrelationships between variables and describe the SWOT matrix and the balanced scorecard strategy map matrix to improve management performance.